Beyond Poverty Escapes—Social Mobility in Developing Countries: A Review Article. (19th August 2019) - Iversen, Vegard; Krishna, Anirudh; Sen, Kunal
Abstract: While social mobility in advanced economies has received extensive scholarly attention, crucial knowledge gaps remain about the patterns and determinants of income, educational, and occupational mobility in developing countries. Focusing on intergenerational mobility, we find that estimates often differ greatly for the same country, depending on the concept and measure of mobility used, on variable constructions and on the data set utilized. There is also wide variation in mobility across regions and social groups. We discuss data and income and other variable measurement challenges when agriculture and the informal sector absorb most of the workforce, and illustrate why occupational classifications and widely used mobility measures may perform less well in such settings. Factors beyond those featuring in the literature on advanced economies are plausible determinants of social mobility, particularly of what we call moderate and large ascents (and descents), in developing country contexts. We highlight the lack of in-depth understanding of the multiple and often localized hurdles to such more pronounced progress. Similar knowledge gaps exist for large descents, which give rise to particularly profound concerns in low-income settings. We report and touch on the implications of suggestive findings of a disconnect between educational and occupational mobility. Innovative research requires critical engagement with theory and with methodology, identification, and data challenges that may overlap or deviate notably from those encountered in advanced economies.